2019
DOI: 10.1007/s10006-019-00748-3
|View full text |Cite
|
Sign up to set email alerts
|

Does postoperative orbital volume predict postoperative globe malposition after blow-out fracture reconstruction? A 6-month clinical follow-up study

Abstract: Purpose The aim of this study was to investigate the relationship between intraorbital volume change caused by orbital fracture and globe malposition (GMP) in blow-out fracture patients undergoing surgery and to clarify the significance of different radiologically detected predictors associated with GMP. Patients and methods A 6-month prospective follow-up study of unilateral isolated orbital fractures was designed and implemented. The main outcome variable was GMP (pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 23 publications
0
8
0
2
Order By: Relevance
“…Devido a complexa anatomia da região e ao frequente acometimento do globo ocular, fraturas de paredes da órbita, podem apresentar diversas complicações, com alta morbidade, dentre as quais destaca-se a redução do nível de consciência do paciente (Felding et al, 2016; As fraturas de órbita podem apresentar padrões isolados ou envolver outras estruturas ósseas e de tecido mole, como por exemplo, as fraturas do complexo zigomático-maxilar e as fraturas naso-órbito-etmoidais (Rajkumar et al, 2015;Hartwig et al, 2019). A correlação entre o aumento do volume da órbita, verificado por meio de exames complementares, e o desenvolvimento de alterações clínicas tem sido frequentemente discutida na literatura atual (Schönegg et al, 2018;Snäll et al, 2019). Alhamdani et al (2015) descrevem as principais injúrias oftalmológicas após trauma em face cursando com fraturas em parede de órbita, são elas: hifema, midríase traumática, abrasão da córnea e equimose conjuntival.…”
Section: Resultsunclassified
“…Devido a complexa anatomia da região e ao frequente acometimento do globo ocular, fraturas de paredes da órbita, podem apresentar diversas complicações, com alta morbidade, dentre as quais destaca-se a redução do nível de consciência do paciente (Felding et al, 2016; As fraturas de órbita podem apresentar padrões isolados ou envolver outras estruturas ósseas e de tecido mole, como por exemplo, as fraturas do complexo zigomático-maxilar e as fraturas naso-órbito-etmoidais (Rajkumar et al, 2015;Hartwig et al, 2019). A correlação entre o aumento do volume da órbita, verificado por meio de exames complementares, e o desenvolvimento de alterações clínicas tem sido frequentemente discutida na literatura atual (Schönegg et al, 2018;Snäll et al, 2019). Alhamdani et al (2015) descrevem as principais injúrias oftalmológicas após trauma em face cursando com fraturas em parede de órbita, são elas: hifema, midríase traumática, abrasão da córnea e equimose conjuntival.…”
Section: Resultsunclassified
“…However, Young et al 25 reported a mean residual enophthalmos of 2.1 mm to be clinically irrelevant, and it seems like most non-surgically treated patients don't have aesthetically disfiguring enophtalmos after 12month follow-up 26 . Additionally, enophthalmos can persist even after successful surgery 27 . This makes it extremely difficult to evaluate the need for surgical intervention solely based on radiological findings.…”
Section: Discussionmentioning
confidence: 99%
“…However, in patients who display postoperative PE, overcorrection of orbital volume can also result in GMP with as little as 1.15 ml of volume correction. 15…”
Section: Accepted Manuscriptmentioning
confidence: 99%